2016
DOI: 10.5194/bg-13-1677-2016
|View full text |Cite
|
Sign up to set email alerts
|

Impact of ocean acidification on phytoplankton assemblage, growth, and DMS production following Fe-dust additions in the NE Pacific high-nutrient, low-chlorophyll waters

Abstract: Abstract. Ocean acidification (OA) is likely to have an effect on the fertilizing potential of desert dust in high-nutrient, low-chlorophyll oceanic regions, either by modifying iron (Fe) speciation and bioavailability or by altering phytoplankton Fe requirements and acquisition. To address this issue, short incubations (4 days) of northeast subarctic Pacific waters enriched with either FeSO4 or dust and set at pH 8.0 (in situ) and 7.8 were conducted in August 2010. We assessed the impact of a decrease in pH o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 73 publications
4
9
0
Order By: Relevance
“…1d−f), thus confirming that Fe-limitation was relieved and phytoplankton growth was stimulated through addition of either FeCl 3 or dust. In fact, enrichment by dust showed similar trends in F v /F m relative to FeCl 3 amendment irrespective of the pCO 2 , suggesting that dust can successfully relieve Fe-limitation, as previously observed (Mélancon et al 2016, Conway et al 2016. Accordingly, total dFe concentrations increased initially after Fe enrichment (dust and FeCl 3 ) whereas no significant differ-ences in total dFe were observed at the end of the first phase (Table 1).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…1d−f), thus confirming that Fe-limitation was relieved and phytoplankton growth was stimulated through addition of either FeCl 3 or dust. In fact, enrichment by dust showed similar trends in F v /F m relative to FeCl 3 amendment irrespective of the pCO 2 , suggesting that dust can successfully relieve Fe-limitation, as previously observed (Mélancon et al 2016, Conway et al 2016. Accordingly, total dFe concentrations increased initially after Fe enrichment (dust and FeCl 3 ) whereas no significant differ-ences in total dFe were observed at the end of the first phase (Table 1).…”
Section: Discussionsupporting
confidence: 81%
“…Furthermore, similar total dFe concentrations were measured within the respective Fe treatments under both pCO 2 levels (Table 1), even for the dust treatment, supporting previous observations that the effect of OA on Fe(III)' solubility is rather small in seawater over the pH range of 7.5 to 9 (Kuma et al 1996, Liu & Millero 2002, Fishwick et al 2014. Hence, our results suggest that Fe solubility associated with dust was not significantly enhanced under OA as previously ob served (Fishwick et al 2014, Mélancon et al 2016. Previous studies, however, reported changes in Fe(III) complexation, resulting in a decline in the bioavailability of Fe(III) to marine phytoplankton (Shi et al 2010, Sugie et al 2013.…”
Section: Discussionsupporting
confidence: 72%
“…The study by Louis et al (2018), carried out with filtered (0.2 µm mesh size) natural seawater using the same dust analogue and flux as in the present study, showed that even an extreme ocean acidification scenario (∼ −0.6 pH units) does not impact the bioavailability of macro-and micro-nutrients (NO x , DIP and DFe) in the oligotrophic northwestern Mediterranean Sea. Similar results were found by Mélançon et al (2016) in high-nutrient lowchlorophyll (HNLC) waters of the northeastern Pacific, under a moderate ocean acidification scenario (−0.2 pH units). As no differences were observed for NO x and DIP concentrations within a few hours following dust addition under present and future environmental conditions, our results agree with these previous findings and further highlight the absence of a direct effect of ocean warming (+3 • C) on the release of nutrients from atmospheric particles.…”
Section: Impact Of Dust Addition Under Future Environmental Conditionssupporting
confidence: 79%
“…Atmospheric deposition is well recognized as a significant source of micro-and macro-nutrients for surface waters of the global ocean (Duce et al, 1991;Jickells et al, 2005;Moore et al, 2013). The potential modulation of the biological carbon pump efficiency and the associated export of carbon by atmospheric deposition events are still poorly understood and quantified (Law et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, previous studies found that acidification could decrease the postfertilization success and affect the growth, development, and physiological energetics of sea cucumbers (Yuan et al, 2015(Yuan et al, , 2016. Moreover, seawater acidification changes the seawater carbonate system, which could affect the marine ecological environment (Orr et al, 2005;Jian et al, 2019), and thus affect the marine primary productivity and community structure (Josiane et al, 2016) and the microbial composition and function (Lidbury et al, 2012;Kerfahi et al, 2020). Previous studies indicate that increased temperature is a driving abiotic factor in reshaping bacterial communities in the marine ecosystem (Smale et al, 2017;Mensch et al, 2020).…”
Section: Introductionmentioning
confidence: 99%